Industrial clusters and peripheral areas - Pontes, José Pedro (2022)
This paper is an appraisal of the economic feasibility of the location of clusters of firms in peripheral areas. In a spatial economy formed by two asymmetric regions, an upstream firm supplies an input to two downstream firms. This economy is modelled as a three-stage noncooperative game. In the first stage, the firms choose locations simultaneously. In the second stage, the upstream firm selects a monopoly price for the downstream firms. In the third stage, the final good firms compete in quantities, taking the input price as given. If it is assumed that each firm is active in each market, the agglomeration of all firms in the large region is always a perfect equilibrium, although it need not be unique. If vertical linkages are intermediate and transport costs are high, there is a dispersed equilibrium with the upstream firm in the small region. If vertical linkages are strong and transport costs are low, a cluster can occur in the small region. In this latter case, regional policy can select the small peripheral region as a location for the industrial cluster